Enhanced electrochemical advanced oxidation on boride activated carbon: The influences of boron groups. (20th December 2021) - Chen, Xu; Wang, Lida; Sun, Wen; Yang, Zhengqing; Jin, Jingjing; You, Danni; Liu, Guichang
Abstract: Exploring an efficient electro-catalyst is fundamentally important to enhance degradation of persistent organic pollutants during electrochemical advanced oxidation process. In this work, boride activated carbon (BAC) containing different boron group content was prepared as low-cost and efficient catalysts. BAC possessed a more positive onset potential of oxygen reduction reaction (0.458 V vs. RHE) and a faster rate of H2 O2 generation (365 mg/L pH=3), compared with activated carbon (0.425 V vs. RHE, 138 mg/L pH=3). DFT calculations and XPS results revealed that -BC3 and -BC2 O active groups enhanced oxygen adsorption, and small electronegativity difference between B and O facilitated the desorption of OOH. The rate of in-situ phenol degradation (0.193 min −1 ) increased by an order of magnitude as compared to activated carbon (0.018 min −1 ), because BAC promoted the in-situ conversion of H2 O2 to OH. Therefore, it provided a theoretical base for the further application of boron catalyst in two-electron oxygen reduction process. Graphical abstract: Image, graphical abstract